Investing in Teacher Learning: In-service Teacher Professional Training in Indonesia - Umar Abdullah (LINGUA: Jurnal Bahasa dan Sastra, 2017)
Abstract: This study aimed to find out what happen in a 10-day in-service teacher professional training in Indonesia, commonly known as PLPG. A qualitative study using observations and document analysis was used as the research procedure. It was found that PLPG offered teachers substantial learning experiences covering professional and pedagogical competencies, necessary for teachers to achieve a professional level of quality in their duties. In addition, the activities featured in PLPG were in line with constructivist theory in that they seek to foster teacher-to-teacher interaction through active, contextualized, and collaborative modes of learning. The study suggests the need of a system of peer support and feedback integrated into long-term trainings, and extensively well-designed content-related continuing teacher professional development to improve and sustain teachers’ teaching practices. Key words: teacher learning; teacher certification; teacher professional development, teacher education Abstrak: Penelitian ini bertujuan untuk melihat secara seksama pelaksanaan Pendidikan dan Latihan Profesi Guru (PLPG) di Indonesia. Data penelitian kualitatif ini diperoleh melalui observasi dan analisis dokumen. Riset ini menemukan bahwa PLPG menawarkan pengalaman belajar yang subsbtansial kepada guru yang mencakup kompetensi profesional dan pedagogis, dimana kedua kompetensi ini sangat diperlukan guru sebagai syarat menjadi guru yang profesional. Selain itu, kegiatan yang dilaksanakan dalam PLPG sejalan dengan teori konstruktivis yang mendorong terjadinya interaksi diantara peserta pelatihan melalui metode pembelajaran yang aktif, kontekstual, dan kolaboratif. Riset ini memberikan beberapa rekomendasi, yaitu perlunya dukungan dan umpan balik teman sebaya yang terintegrasi dalam pelatihan jangka panjang, dan perlunya pengembangan profesi guru berkelanjutan yang dirancang secara ekstensif untuk meningkatkan dan mempertahankan praktik pengajaran guru yang berkualitas.Kata-kata kunci: pembelajaran gur, sertifikasi guru, pengembangan profesi guru, Pendidikan guru.